Coordinated caching scheme based on popular content awareness and tracking - Guo ZHANG; Yu-xiang HU; Wan-wei HUANG; Bin-qiang WANG; Lu-jia CAO (Tongxin xuebao)
To overcome the problems of the on-path caching schemes in the content centric networking,a coordinated caching scheme based on the node with the max betweenness value and edge node was designed.According to the topol-ogy characteristics,the popular content was identified at the node with the max betweenness value and tracked at the edge node.The on-path caching location was given by the popularity and the cache size.Simulation results show that,com-pared with the classical schemes,this scheme promotes the cache hit ratio and decreases the average hop ratio,thus en-hancing the efficiency of the cache system.